The distribution of antibiotic resistance genes in plasmids and genomic islands of Acinetobacter baumannii through whole genome sequencing - Vo, Thi Bich Thuy; Tran, Thi Hop; Nguyen, Thi Diem; Huynh, Thi Thu Hue; Le, Thi Nguyen Binh; Nghiem, Ngoc Minh (Vietnam Journal of Biotechnology, 2025)
Acinetobacter baumannii is a prominent pathogen in hospital environments, capable of causing various serious infections. The opportunistic pathogen A. baumannii contains variants of the AbaR genomic islands, which enhance its multidrug resistance capabilities. Whole genome sequencing (WGS) identified 36 plasmids across 30 samples, with 10 plasmids present in at least 5 samples; notably, 19 out of 36 plasmids contain antibiotic resistance genes. Plasmid AE271 was found in 18 samples that harbored important beta-lactam resistance genes, including blaOXA-91, blaOXA-120, blaOXA-67, and blaOXA-66. Both plasmids AC163 and AE689 have carried blaOXA-23, a commonly found resistance gene in A. baumannii. Plasmid AC715 was present in 10 samples, including a variety of resistance genes such as blaOXA-23, aph(3’)-VIb, and sul2. Plasmid AC237, identified in 9 samples, also contains multiple resistance genes, including sul1, armA, and msr(E), reflecting its diversity in drug resistance. Some plasmids were classified as "novel," containing the blaOXA-23 gene. Integrative antibiotic resistance elements (REIs) such as AbaR4 and Tn6167 confer carbapenem resistance, an essential antibiotic group for treating A. baumannii infections. Several REIs, including AbaR22, Tn6166, and delta-AbaR25, exhibit antibiotic resistance, including aminoglycosides, tetracyclines, sulfonamides, and beta-lactams. This finding underscores the complex genetics of plasmids in A. baumannii and their role in the spread of antibiotic resistance. The study also indicates that genomic islands may play a significant role in spreading antibiotic resistance genes, providing deeper insights into the diversity and genetic organization of RIs in A. baumannii populations that have yet to be explored.